Karakter Morfologi dan Genetik Lunella sp. - Simon P.O Leatemia; Isma Isma; Thomas F Pattiasina; Dandi Saleky (Universitas Musamus, Merauke, Papua, 2021)
Environmental degradation and the utilization of excess are very influential in a reduction of thepotential of Turbinidae Gastropod Resources. Morphology of shells can changes due to adaptation tothe surrounding environment resulting in misidentification. This study aims to analyze morphology andmolecular character of Turbinidae. Morphometric analysis is done by comparing the measureddimensions of the shell, while the molecular identification is done by using the DNA barcoding usingCOI gene to species identification. The results showed a comparison of growth between thedimensions shell of the Lunella sp. showed the negative allometric and positive allometric. Characterof shell growth between dimensions of the Lunella sp. shows the negative allometric and positiveallometric. Molecular analysis identified Turbinidae was found Lunella sp. its similar to DNAsequence Lunella sp. Sulawesi. The molecular analysis identifies Turbinidae found is Lunella sp. withsimilarities of 98.41 and 98.31%. The environmental conditions can affect change the morphology andgenetic of Turbinidae. DNA barcoding has been successful to identify Turbinidae gastropods.